Democratizing EU democracy support in Uganda: embedding democracy aid within local negotiations of justice in Acholiland. Issue 8 (17th November 2022) - Vandeputte, Nathan
ABSTRACT: This article scrutinizes the way the European Union's (EU) democracy aid corresponds to how "a just society" is negotiated among the Acholi – an ethnic group in Northern Uganda. Through document analysis of EU aid projects, qualitative interviews with project implementers and through secondary analysis of ethnographic literature, this article finds that EU democracy aid in Acholiland – through its emphasis on individual responsibility, entrepreneurship, and its exclusion of elders – selectively aligns with the life worlds of urban youths. Such approach, however, risks further antagonizing Acholi social cohesion. As such, this article points attention to the fact that democracy support will always intervene in a contentious debate on what is perceived as locally just and whom participates in such negotiation. When considering questions of how international democracy support could be improved, it is, therefore, necessary to first of all deconstruct the validity of one's underlying conceptions of what is a just political order, and secondly, to acknowledge that any reconstruction on the grounds of including a plurality of alternatives will always require a political intervention. Such considerations, it is argued, would open up the debate on improving EU democracy support to concerns of how such democracy support itself can become more democratic.